Tailoring of electron flow current in magnetically insulated transmission lines - J. P. Martin; M. E. Savage; T. D. Pointon; M. A. Gilmore (Physical Review Special Topics. Accelerators and Beams, 2009)
It is desirable to optimize (minimizing both the inductance and electron flow) the magnetically insulated vacuum sections of low impedance pulsed-power drivers. The goal of low inductance is understandable from basic efficiency arguments. The goal of low electron flow results from two observations: (1) flowing electrons generally do not deliver energy to (or even reach) most loads, and thus constitute a loss mechanism; (2) energetic electrons deposited in a small area can cause anode damage and anode plasma formation. Low inductance and low electron flow are competing goals; an optimized system requires a balance of the two. While magnetically insulated systems are generally forgiving, there are times when optimization is crucial. For example, in large pulsed-power drivers used to energize high energy density physics loads, the electron flow as a fraction of total current is small, but that flow often reaches the anode in relatively small regions. If the anode temperature becomes high enough to desorb gas, the resulting plasma initiates a gap closure process that can impact system performance. Magnetic-pressure driven (z pinches and material equation of state) loads behave like a fixed inductor for much of the drive pulse. It is clear that neither fixed gap nor constant-impedance transmission lines are optimal for driving inductive loads. This work shows a technique for developing the optimal impedance profile for the magnetically insulated section of a high-current driver. Particle-in-cell calculations are used to validate the impedance profiles developed in a radial disk magnetically insulated transmission line geometry. The input parameters are the spacing and location of the minimum gap, the effective load inductance, and the desired electron flow profile. The radial electron flow profiles from these simulations are in good agreement with theoretical predictions when driven at relatively high voltage (i.e., V≥2  MV).